ANALISIS PERENCANAAN DAN PENGENDALIAN PERSEDIAAN PRODUK MESIN MEREK MODERN PADA UD. BUMI MAS SAMARINDA - Ida Rahmawati3, Fitri Artiningsih1 Titin Ruliana 2 (EKONOMIA, 2021)
Planning and controlling mechanism of merchandise inventory at UD. Bumi Mas Samarinda is received by the company from the sales profit of Modern brand machines which are sold in the market. The sales mechanism is caused by a lack of careful planning in determining inventory, because companies place orders based on estimates without a detailed method, only referring to the remaining stock of goods available. The aim of this research is to know and analyze the planning and control of inventory of Modern brand machine products at UD. Bumi Mas Samarinda in 2017-2019 has been optimal.The theoretical basis used is Financial Management with data analysis tools using the calculation of Economic Order Quantity (EOQ), safety stock, reorder point, and optimal.The results showed that the inventory planning of Modern brand machine products at UD. Bumi Mas Samarinda, there was an increase and decrease in the remaining inventory due to UD. Bumi Mas Samarinda lacks analysis in managing supplies. And the results of research from inventory control of Modern brand machine products at UD. Bumi Mas Samarinda is seen from the calculation of Economic Order Quantity (EOQ), safety stock, reorder point, and optimal results show that the results fluctuate every year.